Parenting values moderate the intergenerational transmission of time preferences - Anne Ardila Brenøe; Thomas Epper (University of Zurich, Department of Economics, 2019)
We study the intergenerational transmission of time preferences in a setting without reverse causality concerns. We find substantial transmission of patience from parents to children, which is insensitive to the inclusion of comprehensive sets of administratively reported controls and persists as children age. We further explore heterogeneity in the transmission with respect to two theoretically important but distinct dimensions of socialization through which parents can influence children's traits: parenting values and parental involvement. Our results show that, in contrast to authoritative parents, authoritarian and permissive parents transmit patience to their offspring. Meanwhile, parental involvement is not an important moderator. These patterns replicate in an independent sample with richer measures of parental involvement.
Keywords: D15; J12; J24; J62; 330; intergenerational transmission; time preferences; patience; parenting style; parenting values; parental involvement